2010
DOI: 10.3390/molecules15031442
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Study of a Novel Macrocyclic Chiral(Salen) ligand and its Uranyl and Mn Complexes

Abstract: A novel chiral macrocyclic ligand incorporating a chiral salen moiety into a framework containing two biphenyl units was synthesized. Structural properties and conformational aspects of the free ligand and an UO2 complex were studied by using NMR spectroscopy in solution and MM calculations. The Mn(III) complex was tested as catalyst in enantioselective oxidation of prochiral unfunctionalized olefins to the corresponding optically active epoxides under very mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The stereochemistry and conformation of di-Schiff bases containing calix [4]arene unit U(IV) complexes have been deduced on the basis of the 2D TOCSY and T-ROESY measurements. 116 Amato et al 117 analysing the T-ROESY data have shown that formation of the uranyl(VI) complex maintained the symmetrical structure of the Schiff base containing two biphenyl units. The lack of dipolar contacts between aromatic rings as well as between aromatic protons and isohexyloxy substituents suggested the presence of less hindered discshaped complex conformation in solution.…”
Section: U(iv) Complexesmentioning
confidence: 97%
“…The stereochemistry and conformation of di-Schiff bases containing calix [4]arene unit U(IV) complexes have been deduced on the basis of the 2D TOCSY and T-ROESY measurements. 116 Amato et al 117 analysing the T-ROESY data have shown that formation of the uranyl(VI) complex maintained the symmetrical structure of the Schiff base containing two biphenyl units. The lack of dipolar contacts between aromatic rings as well as between aromatic protons and isohexyloxy substituents suggested the presence of less hindered discshaped complex conformation in solution.…”
Section: U(iv) Complexesmentioning
confidence: 97%
“…ee values were determined by capillary GLC analysis employing chiral columns for styrene, cis-substituted styrenes and 1,2-dihydronaphthalene epoxides, and by both GLC analysis and 1 H-NMR measurements in the presence of Eu(+)(hfc) 3 shift reagent for chromene epoxides. 14 The comparative catalytic activities of 3a and 3b are reported in Table 1.…”
Section: Catalysismentioning
confidence: 99%
“…Over the past decades great attention has been devoted to the design and synthesis of Schiff bases with enhanced ability to selectively encapsulate the given metal ion (16) . A large number of macrocycles and their complexes with metal ion have been synthesized and characterized (17)(18)(19) . A literature search reveals that a large number of hexaazamacrocyclic metal complexes have been prepared and characterized (18)(19)(20) .…”
Section: Introductionmentioning
confidence: 99%